Ivan Grozny Volcano (Iturup Island, Kuril Islands): Composition of Erupted Materials and Modern Activity - Zharkov R.V.; Bergal-Kuvikas Olga; Degterev A.V.; Romanyuk F.A.; Borisovsky S.E. (Pleiades Publishing, Ltd., 2024)
The paper summarizes data on the historical activity of Ivan Grozny volcano (Iturup Island, Kuril Islands), including the results of original studies of sulfur hydrothermal and eruptive activities of the volcano since 2004. New chemical data on the volcanic edifice rocks and pyroclastics of the last explosive eruption in 2012–2013 are presented. The composition of the volcanic edifice rocks varies from andesites to dacitic andesites (58.16–61.42 wt % SiO2) of the medium potassium series (0.93–1.14 wt % K2O). Pyroclastics from the 2012–2013 explosive eruption chemically correspond to andesites (57.20–59.54 wt % SiO2) with moderate potassium contents (0.95–1.05 wt % K2O). According to microprobe studies, glasses have much more felsic compositions. The values obtained are similar to the geochemical compositions of the products of the 1973 and 1989 eruptions. Taking into account the dominant wind regime in central Iturup Island, the hazard from ashfalls from future eruptions of Ivan Grozny volcano is estimated, indicating the predominant ash spread in the northwestern, western, and southwestern directions.
Keywords: 38.37.25 Вулканология; Иван Грозный